Mapping Poverty Alleviation in Garut Regency: An Actor-Network Theory Perspective on Collaboration and Actor Interactions - Gugun Geusan Akbar; Muchtar Muchtar; Pupung Pundenswari; Seriwati Ginting (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This study investigates the essential yet frequently ignored function of trust in data governance networks for poverty alleviation programs in Garut Regency, Indonesia, based on Actor-Network Theory (ANT). The research employed a qualitative method which included 35 in-depth interviews with government officials from Social Service, Regional Planning Agency, and Baznas together with beneficiary community members and Focus Group Discussions with Regional Government Organizations and Village Heads. The research demonstrates that poor trust between human actors (government-community) and non-human actors (Poverty Data) creates major obstacles for essential poverty alleviation programs including Non-Cash Food Assistance and the Family Hope Program. The main obstacles that emerged during the study included strong sectoral egos, uncoordinated and non-unified data systems and unclear data management transparency practices. According to ANT